The EU, NATO and the integration of Europe : rules and rhetoric - Schimmelfennig, Frank, 1963- (Themes in European governance., 2003)
Frank Schimmelfennig analyzes Eastern enlargement of the European Union and NATO and develops an original theory to explain why it occurred. Backed by original data, he argues that expansion to the East can be understood in terms of liberal democratic values and the shaming of opponents.